2015
DOI: 10.3390/w7031232
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Spatio-Temporal Variability of Annual Minimum Daily Extreme Flow Characteristics as a Function of Land Use and Dam Management Mode in Quebec, Canada

Abstract: This study presents a comparison of the spatio-temporal variability of characteristics (magnitude, duration and timing) of annual minimum daily extreme flows (AMEF) as a function of land use and the mode of management of dams. Streamflow measured at stations not affected by dams at Joliette, along the L'Assomption River (agricultural watershed, 1340 km 2 ), and at Saint-Michel-des-Saints, on the Matawin River (forested watershed, 1390 km 2 ) on one hand, and downstream from the Rawdon dam (regulated natural-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In other words, variations in streamflow increase significantly over time in both watersheds. In the agricultural watershed, this increase may be related to increasing rainfall [18,22], while in the forested watershed, only summer rainfall has increased significantly. In addition, minimum temperatures have also increased significantly in the four seasons [18].…”
Section: Comparison Of the Temporal Variability Of Flow Rate Change Imentioning
confidence: 98%
See 2 more Smart Citations
“…In other words, variations in streamflow increase significantly over time in both watersheds. In the agricultural watershed, this increase may be related to increasing rainfall [18,22], while in the forested watershed, only summer rainfall has increased significantly. In addition, minimum temperatures have also increased significantly in the four seasons [18].…”
Section: Comparison Of the Temporal Variability Of Flow Rate Change Imentioning
confidence: 98%
“…Two watersheds met these three criteria, namely the adjacent L'Assomption River and Matawin River watersheds. These watersheds have already been described in detail in some of our previous work [18,22]. The Matawin River watershed is fully contained within the Canadian Shield.…”
Section: Description Of Watershedmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrological changes induced by the diversion dam built on the Manouane River are different from this general scheme, because that dam did not affect maximum daily flows, but produced a significant decrease in minimum daily flows. Previous work looking at the hydrological impacts of dams in Quebec distinguished three types of impacts, each corresponding to a specific dam management mode [1,[29][30][31][32][33][34]. The first type of hydrological impact is characterized by a decrease in annual and seasonal maximum and minimum daily flows.…”
Section: Annual and Seasonal Maximum Daily Flowsmentioning
confidence: 99%
“…As far as human factors are concerned, many dams have been built in Quebec since the nineteenth century to develop natural resources and fulfill the demand for both domestic and industrial hydroelectric power [4]. Many studies have looked at the impacts of these works on streamflow [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and have shown that the extent of changes in streamflow downstream from these dams depends, among other things, on the dam management mode. Four management modes have been identified and described, each corresponding with a specific regulated hydrological regime downstream from dams.…”
Section: Introductionmentioning
confidence: 99%